2021
DOI: 10.1016/j.bbrep.2021.100993
|View full text |Cite
|
Sign up to set email alerts
|

PCR-RFLP and FTIR-based detection of high-risk human papilloma virus for cervical cancer screening and prevention

Abstract: Background Approximately 70% of cervical carcinoma cases show the presence of high-risk Human Papilloma Virus (HPV), especially HPV-16 and HPV-18, and can be used to stratify high risk patients from low risk and healthy. Currently, molecular biology techniques such as polymerase chain reaction (PCR) are used to identify the presence of virus in patient samples. While the methodology is highly sensitive, it is labor intensive and time-consuming. Alternative techniques, such as vibrational spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…PCR-based methods are considered to be the current gold standard for virus detection [37,38]. Due to the amplification of specific nucleic acid sequences, viruses can be identified in a sensitive and highly specific manner [38,39].…”
Section: Virus Detectionmentioning
confidence: 99%
See 3 more Smart Citations
“…PCR-based methods are considered to be the current gold standard for virus detection [37,38]. Due to the amplification of specific nucleic acid sequences, viruses can be identified in a sensitive and highly specific manner [38,39].…”
Section: Virus Detectionmentioning
confidence: 99%
“…Therefore, it is difficult to isolate them from the sample fluid and as described above they are often bound to nanoparticles or antibodies for isolation and quantification. In clinical surroundings, standardized tests based on PCR methods are used for viral load determination [37,39]. Since a higher viral load correlates with the severity of the infection, many different optical approaches-like fluorescence microscopy, vibrational spectroscopy-are being explored to detect viral particles [83].…”
Section: Detection Of Viral Loadmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on a patient cohort of 40 HIV positive pregnant women and 80 uninfected controls, they received a classification accuracy of 89% using a DA algorithm. In another study, it was shown how FTIR can detect HPV in cervical fluid samples with a classification of 100% efficiency within the spectral ranges 1400–1800 cm -1 [159] and furthermore could differentiate between low risk HPV and high risk HPV with 71–75% efficiency. ATR-FTIR has thus proven to be a very useful method for viral diagnosis, not only is it rapid and cost effective technique and coupled with only a minuscule amount of body fluid is needed for accurate results, making this method a good candidate to translate to the clinical benchtop [33] .…”
Section: Vibrational Spectroscopic Analysis Of Viruses and Viral Infe...mentioning
confidence: 99%